EFFICACY OF TAMSULOSIN IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA IN TERMS OF TRIAL WITHOUT CATHETER, A RANDOMIZED CONTROL TRIAL - Farhan Khan; Usman Qamar; Muhammad Saifullah; Muhammad Sheraz Javed; Ahsan Ali Arain; Muhammad Sohail; Murli Lal (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Benign prostatic hyperplasia (BPH) is a prevalent cause of voiding problems in older males and is most commonly associated with acute urological complications, most important of which is acute urinary retention (AUR). α1- antagonists are the treatment of choice for the management of patients with BPH. Our objective was to evaluate the efficacy of tamsulosin for the treatment of patients with AUR due to BPH in terms of trial without catheter (TWOC). METHODOLOGY: This randomized control trial was conducted in a Urology Section, Department of Surgery, SIUT Karachi, from 21-12-2016 to 20-06-2017. Our study included 136 patients who presented AUR due to BPH as per selection criteria. Patients were randomized into two groups. Group A patients received tamsulosin (0.4 mg), and group B patients received placebo drug immediately after insertion of Foley catheter. The success of TWOC was evaluated after 3 days of medical treatment. Statistical analysis was carried out using SPSS v20.0. RESULTS: The mean age of the study patients was 59.45 + 8.05 years. The mean duration of BPH disease was 15.39 + 6.84 months. There were 33 (48.5%) patients in the tamsulosin group in which TWOC was successful and only 22 (32.4%) patients in placebo group in which TWOC was successful (p-value 0.04). There was no effect of age and duration of BPH disease on the outcome of this study. CONCLUSION: Tamsulosin is effective for the treatment of patients with AUR due to BPH.